The Impact Of Age, Gender, And Ethnic Diversity On Organizational Performance: An Empirical Study Of Bangladesh's Banking Sector - Roy, Sanjoy Kumar (Goodwood Publishing, 2022)
Purpose: This study aims to investigate the impact of workforce diversity (in terms of employee age, gender, and ethnicity) on organizational performance in Bangladesh's banking sector. Research Methodology: This research work evaluates the relationship between workforce diversity and organizational performance in the banking sector. The impact of workforce diversity on organizational performance is examined using structural equation modeling (SEM). The sample data was acquired from ten randomly chosen banks in Dhaka, Bangladesh, using a standardized questionnaire and a personal survey. Results: The study's findings revealed that age, gender, and ethnic diversity have a statistically significant positive impact on organizational performance. Among them, age diversity has the most significant effect on organizational performance, and gender diversity has less impact. Limitations: Other workforce diversity factors (such as religion, nationality, and so on) may have an impact on organizational performance, but they were not considered in this study. Contribution: The findings of this study reveal that in Bangladesh's banking business, there is a dynamic relationship between workforce diversity and organizational performance. Furthermore, this research work has significant ramifications, as well as the fact that effectively managing diversity practices in the workforce will improve the organization's performance.